2021
DOI: 10.5999/aps.2020.01620
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of the treatment of postaxial polysyndactyly of the foot: Comparison of surgical results after removal of the fifth or sixth toe

Abstract: Background In postaxial polysyndactyly of the foot, the choice of which toe to excise is controversial. It is often treated by resection of the fifth toe to save the lateral neurovascular bundles of the sixth toe. However, the sixth toe is often short and laterally deviated, which may require wedge osteotomy, potentially shortening the phalanx and compromising circulation. This study outlines an individualized method to spare the length and axis of the fifth toe in polysyndactyly with a short and deviated sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The use of this flap resulted in excellent cosmetic results when applied in bilateral first web feet syndactyly, as the aims of a graft‐less technique and avoiding incisions in the dorsum of the foot were accomplished (Magdi, 1998; Nash et al, 2016; Niranjan et al, 2005; Woo et al, 2021). Our study demonstrated a solid anatomical evaluation with a rich vascular source for the plantar skin used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this flap resulted in excellent cosmetic results when applied in bilateral first web feet syndactyly, as the aims of a graft‐less technique and avoiding incisions in the dorsum of the foot were accomplished (Magdi, 1998; Nash et al, 2016; Niranjan et al, 2005; Woo et al, 2021). Our study demonstrated a solid anatomical evaluation with a rich vascular source for the plantar skin used.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the use of a skin graft‐less technique in toe syndactyly release follow the same principles for syndactyly reconstruction in the hand: improving cosmesis by avoiding the use of skin graft and the use of dorsal incisions, and decreasing the risk of web creeping (Hikosaka et al, 2009; McCombe & Soldado, 2021; Say et al, 2021; Tian et al, 2017; Woo et al, 2021). Thus, we opted for the design of a plantar vascularized flap mimicking the one described in the palm by Soldado et al (McCombe & Soldado, 2021; Soldado et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For cases without syndactyly, lateral toe resection was preferred regardless of the involved ray. Corrective osteotomy of the proximal phalanx 12 was not routinely performed, even in patients with a laterally deviated proximal interphalangeal (PIP) joint. A longitudinal Kirschner wire was placed in patients with a large skin graft or skeletal reconstructive procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Pain, biomechanical problems of mobility and function, difficulty with footwear, sensitivity when walking, and aesthetic concerns are the factors that can influence the decision to undergo surgery (Figure 3). 9,13 …”
Section: Introductionmentioning
confidence: 99%
“…Critically, there is a lack of consensus on an ideal approach to surgical management. 8,9 This controversy is greatest when deciding on the appropriate age at which the patient should undergo surgery. 1 Despite this controversy, several authors have proposed different classifications of polydactyly malformation to facilitate management and surgical approach.…”
Section: Introductionmentioning
confidence: 99%